2022
DOI: 10.1071/an21229
|View full text |Cite
|
Sign up to set email alerts
|

Livestock guardian dog protection of free-range poultry from the red fox

Abstract: Context Predation of layer chickens is a major issue for free-range egg producers. Using livestock guardian dogs (LGD) to protect free-ranging poultry is a possible option for producers, although there is little published literature regarding how the dogs protect chickens. Aims This case study was conducted at a free-range egg production farm in Western Australia, where red foxes (Vulpes vulpes) were a common predator of chickens prior to introducing Maremma LGD. We investigated LGD responses to experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Although the property we studied only had two LGDs, this is representative of the use of LGDs for guarding poultry (average of 2.39 LGDs per property reported by other poultry owners surveyed). Individual differences in LGD behavior ( Roddick et al, 2022 ) and the unique situations found on each property ( Campbell et al, 2021 ) somewhat limit generalization of this study, although some underlying findings can be informative about the behavior of LGDs around poultry.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although the property we studied only had two LGDs, this is representative of the use of LGDs for guarding poultry (average of 2.39 LGDs per property reported by other poultry owners surveyed). Individual differences in LGD behavior ( Roddick et al, 2022 ) and the unique situations found on each property ( Campbell et al, 2021 ) somewhat limit generalization of this study, although some underlying findings can be informative about the behavior of LGDs around poultry.…”
Section: Discussionmentioning
confidence: 88%
“…This result suggests a possible disconnect between producer beliefs and expectations towards their LGDs versus the realities of potential distractions and bonding imbalances. Bonding with humans is not desirable because some studies suggest that LGDs do not establish territorial boundaries from which predators are excluded ( Allen et al, 2017 ; Roddick et al, 2022 ; but see van Bommel and Johnson, 2015 ) and therefore the direct presence of the LGD itself is important for protecting livestock. The reality is that LGDs require training ( Rust et al, 2013 ; survey respondents in the present study) and some are likely to need to be restrained to remain with the livestock they are protecting ( van Bommel, 2010 ), although the small size of many poultry production facilities raises the issue of balancing the welfare of the LGDs themselves (providing exercise for mobility and stimulation) as well as that of the livestock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, open areas are used less than ranges with trees because of the antipredatory behavior of hens. Therefore, some key informants mentioned that guard animals seem to be a good solution since they have a noticeable effect on preventing wild birds from landing and staying on the range (see 2.3 Risk of predation) (19). Nevertheless, the introduction of guard animals within the flock is forbidden for sanitary reasons by regulations in most European countries as these animals may themselves carry and transmit bacteria or viruses.…”
Section: Preventing Contaminationmentioning
confidence: 99%
“…Similarly, the Hennovation project found that Alpacas are also effective guard animals as they are social but territorial (74) and some informants also mentioned donkeys as guard animals. However, the use of guard animals in poultry production is still relatively rare and dogs' behavior toward predators still needs investigation (19). The use of netting is more and more widespread, even if nets above wide range areas are difficult to manage and expensive.…”
Section: The Risk Of Predationmentioning
confidence: 99%